2007
DOI: 10.1111/j.1532-950x.2007.00331.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Flexion–Extension Forces in Normal Canine Lumbosacral Cadaver Specimens Before and After Dorsal Laminectomy–Discectomy and Pedicle Screw–Rod Fixation

Abstract: Dorsal laminectomy and partial discectomy does not lead to significant spinal instability. Pedicle screw-rod fixation of L7 and S1 may be used to stabilize an unstable L7-S1 junction in dogs with degenerative lumbosacral stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
78
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(89 citation statements)
references
References 28 publications
3
78
0
8
Order By: Relevance
“…The aim of the PSRFS is to improve deformity and stabilize the spine in its natural position until fusion has occurred and prevent further degenerative changes [7,9] . In veterinary literatures, PSRFS has been only used to stabilize lumbosacral region after laminectomy for treatment of degenerative lumbosacral stenosis in dogs [10,11,14,15] . Furthermore, the system was used to investigate fusion in lumbar vertebrae [16] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of the PSRFS is to improve deformity and stabilize the spine in its natural position until fusion has occurred and prevent further degenerative changes [7,9] . In veterinary literatures, PSRFS has been only used to stabilize lumbosacral region after laminectomy for treatment of degenerative lumbosacral stenosis in dogs [10,11,14,15] . Furthermore, the system was used to investigate fusion in lumbar vertebrae [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The screws were applied to the corpus vertebra of According to the perioperative observation rigid fixation was achieved, even though one level instrumentation. Meij et al [14] reported that dorsal laminectomy and partial discectomy had changed the stiffness characteristics of the spine specimen in neutral zone without changing range of motion, however, in natural cases with degenerative lumbosacral stenosis laminectomy and discectomy could decrease stiffness significantly in vivo. In the case the stiffness of the vertebral region was markedly decreased after discectomy and removal of fractured end plate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Essas características observadas durante o procedimento cirúrgico no caso referido corroboram com Tomlinson (2005), o qual afirma que as principais propriedade do CRIF incluem excelente versatilidade, boa capacidade de contorno (retorcimento), facilidade de aplicação, mínima instrumentação e mínimo contato ósseo, além de ser financeiramente acessível e de força suficiente para permitir carga de peso imediata. No caso relatado, os parafusos foram aplicados exclusivamente nos pedículos vertebrais, no entanto poderia ter sido feita a aplicação dos parafusos envolvendo especificamente os pedículos e os corpos vertebrais de L7 e do sacro, o que possivelmente confere maior rigidez e resistência ao sistema, conforme relataram Meij et al (2007), quando utilizaram parafusos pediculares na coluna lombossacra. Segundo Smolders et al (2012), uma fixação lombossacra em corredores seguros deve ser realizada dorsocaudolateralmente para ventrocraniomedialmente, ou seja, proveniente da cortical dorsal da lâmina até a cortical dorsal do corpo vertebral, sem perfurar a porção cortical ventral assim como as paredes medial e lateral do pedículo.…”
Section: Discussionunclassified
“…Specimens were prepared and tested as described previously [13]. Immediately after euthanasia, the spinal specimens were harvested.…”
Section: Methodsmentioning
confidence: 99%